Multi-Criteria Analysis (Mca) For Fisheries Management In Marine Conservation Area, Kapoposang Islands - Yonvitner Yonvitner; Lukman Faisol; Yasir Yasir; Ilham Ilham (Sam Ratulangi University, 2021)
Multi-criteria analysis has been used widely in the conservation project, especially in the assessment of coastal zones and small islands. In its application to the conservation area, Kapoposang was developing a multi-criteria approach to determine the no-take zone, utilization zone, and sustainable fisheries zone. The multi-criteria approach in Kapoposang constructed by biophysics, ecology, economy and social aspect. Decisions were taken after aggregate analysis of all criteria (Brawn et al 2001) done. The results obtained that the suitable island for the no-take zone is Kapoposang and Suranti Island. Tambakulu Island and Pemangangan were selected as a buffer zone. Finally, the sustainable fisheries zones are Papandangan and Gondongbali island. The spatial analysis of all regional boundaries determined by the three zones reached a total area of 50011.35 ha. Thus the conservation management plan design in each zone were characteristic by different function and management system.Keyword: Zonation, Multi Criteria, Conservation Are, Kapoposang Island, Management plan ABSTRAKAnalisis multi kriteria secara umum sudah sangat luas penggunaanya dalam penelitian konservasi, khusuny untuk penilaian di wilayah pesisir dan pulau-pulau kecil. Dalam hal ini, untuk wilayah konservasi perairan laut Kapoposang, penelitian ini mengujikan pendekatan multi kriteria untuk menentukan kawasan inti, kawasan pemanfaatan dan zona perikanan perikanan berkelanjutan. Pendekatan multi kriteria di kapoposang disusun dari aspek biofisik, ekologi, ekonomi dan social. Keputusan akan diambil setelah analisis agregat dari semua kriteria menurut (Brawn et al 2001) didapatkan. Hasil yang diperoleh menunjukan bahwa pulau cocok untuk kawasan zona inti adalah pulau Kapoposang dan Suranti. PulauTambakulu dan Pemanggangan terpilih sebagai kawasan penyangga. Kemudian zona perikanan berkelanjutan adalah pulau Papandangan dan Gondongbali. Analisis spasial dari semua semua wilayah dikaji tercatat total luas wilayah mencapai 50011.35 ha. Sehingga kemudin rencana aksi konservasi dirancang ditiap zon sesuai dengan perbedaan karakternya serta fungsi.Kata kunci : Zonasi, Multi Kriteria, Konservasi, Kepulauan Kapoposang, Rencana Pengelolaan